ReCOMmendations for management of Preschool ASthma for General Practitioners – COMPAS GP - Zbigniew Doniec (Family Medicine & Primary Care Review, 2016)
Asthma is a chronic, inflammatory, heterogenic disease of the bronchi. It is characterised by bronchial obstruction in the form of wheezing, coughing, shortness of breath and breathing difficulty, showing variable intensity and resolving after medication, or sometimes spontaneously. Making the diagnosis of asthma in children under 5 years of age is based on clinical criteria – the presence of symptoms of bronchial constriction, confirmation of its reversibility and lack of symptoms suggestive of other clinical diagnosis. The criterion for diagnosis are usually three episodes of bronchial obstruction, or a single episode of severe intensity. A detailed history and physical examination allows in most cases to rule out other diseases with similar clinical course. Frequent recurrence of symptoms is an indication for the initial differential diagnosis in primary health care, including a chest X-ray, blood count, often an ENT and/or allergological consultation. However severe, frequent and not responding to treatment episodes of bronchoconstriction indicate the need for diagnostics in specialist hospital wards. Chronic treatment of asthma is based on the administration of anti-inflammatory drugs, inhaled therapy is the treatment of choice in most patients. The assessment of the severity of asthma exacerbation determines the range of treatment, on an outpatient basis consisting of bronchodilators, corticosteroids and oxygen therapy. An important element of treatment is appropriate patient education, with particular attention to the exacerbation risk factors and correct inhalation technique. Children suffering from asthma should be vaccinated against pneumococcal disease and against influenza annually.